The ultrastructure of Sorubim lima (Teleostei, Siluriformes, Pimelodidae) spermatogenesis: premeiotic and meiotic periods - Quagio-Grassiotto, I; Carvalho, E. D. (Churchill Livingstone, 1999)
The ultrastructure of Sorubim lima spermatogenesis during the premeiotic and meiotic periods was studied. Our observations showed that the germ cells in the cysts are connected by cytoplasmic bridges and the mitotic and meiotic divisions are slightly asynchronous, the first and the last spermatogonial generations differ in the cellular and nuclear volume, nucleolus, chromatin condensation, distribution, size, density, and shape of the mitochondria, presence of 'lamellae anulata', amount and dimension of the 'nuages', and movement of the centrioles. In addition to the nuclear prophase structures, the spermatocyte I shows changes in all other cellular organelles and elongated vesicles appear in the cytoplasm. The accentuated cytoplasmic density and thickened walled vesicles are morphological characteristics that differentiate spermatocytes II from the other germ cells in the cysts of Sorubim lima testis. (C) 1999 Harcourt Publishers Ltd.
Keywords: S-lima; teleostei; ultrastructure; spermatogenesis; spermatogonia; spermatocytes